2015
DOI: 10.1182/blood-2015-03-630277
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model recapitulating human monoclonal heavy chain deposition disease evidences the relevance of proteasome inhibitor therapy

Abstract: Key Points• We created the first transgenic mouse model recapitulating the early pathologic features of Randall-type heavy chain deposition disease.• Production of a truncated immunoglobulin heavy chain heightens plasma cell sensitivity to bortezomib via a terminal unfolded protein response.Randall-type heavy chain deposition disease (HCDD) is a rare disorder characterized by glomerular and peritubular amorphous deposits of a truncated monoclonal immunoglobulin heavy chain (HC) bearing a deletion of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 63 publications
(115 reference statements)
5
30
1
Order By: Relevance
“…IgA1 mAb6 and its IgG1 variant were injected in parallel, and kidneys were examined 2 hours later. Deposits formed with IgA1 mAb6 but not with its IgG1 variant (only yielding faint background staining), whereas recently reported transgenic models with monoclonal IgG1 deposition provided a positive staining control 17 (Figure 12).…”
Section: Igg Class Switching Of Iga1 Mab6mentioning
confidence: 78%
See 1 more Smart Citation
“…IgA1 mAb6 and its IgG1 variant were injected in parallel, and kidneys were examined 2 hours later. Deposits formed with IgA1 mAb6 but not with its IgG1 variant (only yielding faint background staining), whereas recently reported transgenic models with monoclonal IgG1 deposition provided a positive staining control 17 (Figure 12).…”
Section: Igg Class Switching Of Iga1 Mab6mentioning
confidence: 78%
“…The CH12 mice feature expression and glomerular kidney deposition of a truncated human-g1 Ig chain cloned in a patient with Randall-type glomerular Ig deposition disease. 17 Three animal facilities were used. The conventional animal facility of the Limoges University, in which multiple pathogens were endemic (including Norovirus, murine hepatitis virus, Staphylococcus aureus, Pasteurella multocida, Syphacia obvelata, and multiple ectoparasites, etc.…”
Section: Animals and Housing Conditionsmentioning
confidence: 99%
“…We performed real-time PCR on selected genes (Herpud1, Hspa5, Ddit3, Xbp1s) and confirmed a similar tendency for upregulation of genes involved in UPR even if, consistent with RNA-Seq analysis, no increase in Xbp1s was observed ( Figure 5D). Having demonstrated that LCDD LC-producing PCs have an exacerbated UPR, we next verified if such ER stress could sensitize PCs to proteasome inhibitors (PI), as we previously showed in a HCDD mouse model (17). We treated mice with suboptimal doses of bortezomib (Bz) for two consecutive days to evaluate the level of PC depletion.…”
Section: Resultsmentioning
confidence: 75%
“…An efficient transgenic strategy to produce high amounts of human pathogenic LCs in mouse. To obtain a high production of the pathogenic human kappa LC, we chose to use a Ig kappa knock-in strategy that proved successful in previous models of Fanconi syndrome and HCDD (17,19). We introduced the VJ exon sequence obtained from a patient (F) with biopsy-proven LCDD in place of the J segments, precluding all further mouse kappa rearrangements in homozygous mice ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation